Simultaneously improved thermal conductivity and mechanical properties of boron nitride nanosheets/aramid nanofiber films by constructing multilayer gradient structure. (15th January 2022) - Zhao, Li-Hua; Wang, Lei; Jin, Yi-Fei; Ren, Jun-Wen; Wang, Zhong; Jia, Li-Chuan
Abstract: Thermally conductive polymer composites (TCPCs) are highly desirable for thermal management in electronic devices and modern electrical systems. However, it still remains a great challenge to reconciliate the conflict between thermal conductivity and mechanical properties of TCPCs. Herein, we realized the development of multilayer gradient boron nitride nanosheet/aramid nanofiber (BNNS/ANF) films with excellent thermal conductivity and improved tensile strength. The multilayer gradient BNNS/ANF films achieved a superior in-plane thermal conductivity of 19.13 W/(m K) and a high tensile strength of 59.3 MPa, with 23.6% and 61.6% increases compared to the single-layer BNNS/ANF film at the same BNNS content. Finite element analysis was used to clarify the enhanced mechanism of the multilayer gradient structure on thermal conductivity and tensile strength. These desirable properties demonstrate that the multilayer gradient structure is an efficient strategy to address the conflict between thermal conductivity and mechanical properties, and paves the way for the design and preparation of high-performance TCPCs for thermal management applications.